AUKUS AS AN EFFECTIVE RESPONSE TO THE PROSPECTIVE LIMITATION OF AMERICAN DOMINATION IN THE INDO-PACIFIC - Mickiewicz, Piotr (Torun International Studies, 2023)
The establishment of the AUKUS system by the USA, Great Britain and Australia is a tangible proof of the change in the American maritime strategy and the rivalry with China for influence in the Indo-Pacific. Including Australia in the efforts to curb Chinese regional expansion is an undoubted success of Washington, which has skilfully used both the weaknesses of the QUAD agreement and the Australia-India-Indonesia trilateral cooperation to persuade Canberra to redefine its policy towards China and the region itself. As a result, Australia is becoming not only the second most important ally of the USA after Great Britain, but also the most important maritime player in the Indian Ocean. This status also poses a threat to the US, as it will weaken the community of interests with India and – to a lesser extent – with Saudi Arabia. Moreover, American politicians must accept the fact that they will be co-makers of policies in the Indo-Pacific region and that sometimes – in their own interest – they will be forced to remain passive in the face of actions taken by Canberra. The aim of the article is to analyze the political significance of the AUKUS agreement for American politics and to assess the possibility of its potential transformation into a political alliance or a regional maritime security complex. This assessment will be made based on the analysis of strategic documents of the signatories of the agreement and political and economic conditions in the Indo-Pacific region. The issue of approval by the American political establishment for recognizing Australia as an independent political player in this region was considered a major threat to the implementation of this political concept.